Eksternalisasi Konflik Internal Yaman Dalam Kerangka Analisis Internationalization of Conflict Theory - Heriamsal, Krisman; Manurung, Felix Broson; Rahmat, Rhin Khairina (Hasanuddin Journal of International Affairs, 2024)
This research discusses the Yemen conflict that was originally internal and then transformed into an international conflict due to the externalization process. The author sees that the increasingly complex development of the Yemen conflict was affected by the intervention of external actors in the conflict. This research aims to find out how Yemen's internal conflict transformed into an international conflict using the analytical framework of the Internationalization of Conflict Theory. Therefore, in examining the externalization of Yemen's internal conflict, the author uses the concept of escalation, with qualitative research methods. The research results show that the externalization of Yemen's internal conflict is demonstrated through the involvement of external actors such as Saudi Arabia and its coalition, the United States, Britain, France, Iran, and ISIS. In this case, the escalation of the Yemen conflict occurred because of the geographical proximity between Yemen and several countries such as Saudi Arabia, the similarity of identity or ideology between internal parties and external parties who intervened in the Yemen conflict, as well as the opportunities and interests of foreign parties in the Yemen conflict.     Penelitian ini membahas tentang konflik Yaman yang semula bersifat internal kemudian mengalami transformasi menjadi konflik internasional karena adanya proses eksternalisasi. Penulis melihat perkembangan konflik Yaman yang semakin kompleks sangat dipengaruhi oleh intervensi pihak asing dalam konflik tersebut. Tujuan penelitian ini adalah mengetahui bagaimana konflik internal Yaman bertransformasi menjadi konflik internasional dengan menggunakan kerangka analisis Internationalization of conflict theory. Oleh karena itu, dalam menelaah eksternalisasi konflik internal Yaman, penulis menggunakan konsep eskalasi, dengan metode penelitian kualitatif. Hasil penelitian menunjukkan bahwa Eksternalisasi konflik internal Yaman ditunjukkan melalui keterlibatan aktor eksternal seperti, Arab Saudi dan koalisinya, Amerika Serikat, Inggris, Prancis, Iran, dan ISIS. Dalam hal ini, Eskalasi konflik Yaman terjadi karena adanya kedekatan secara geografis antara Yaman dengan sejumlah negara seperti Arab Saudi, adanya kesamaan identitas maupun ideologi antara pihak internal dengan pihak eksternal yang mengintervensi konflik Yaman, serta adanya peluang dan kepentingan pihak asing dalam konflik Yaman.